Attitudes of Professors Toward Accounting Ethics. - Bedingfield, James D.; Loeb, Stephen E. (The Accounting Review, 1973)
This article presents information on the attitudes of accounting educators towards the provisions of the AICFA code of ethics. Certified Public Accountants usually have received their first exposure to accounting ethics in accounting courses at colleges and universities. An educator's attitudes towards the provisions of the code may possibly influence his classroom presentation of the code. Consequently, the attitudes toward the code by professors who teach accounting ethics may influence the ethical behavior and attitudes of the practicing profession. Questionnaires were mailed to the accounting department chairmen of 14 universities that have undergraduate programs accredited by the American Association of Collegiate Schools of Business. These individuals were asked to respond to the questionnaire if they were involved with the course in which accounting ethics was taught; if they were not so involved, they were asked to give the questionnaire to the individual in charge of the course in which ethics was taught. Of the respondents 88% agreed that CPAs should not advertise and 89% agreed that CPAs should not attempt to obtain clients by solicitation. Most of the respondents appeared to feel that advertising and or solicitation were not functional.